1979
DOI: 10.1042/bj1820687
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of proton-linked transport systems. The lactose permease of Escherichia coli

Abstract: Evidence is presented that lactose uptake into whole cells of Escherichia coli occurs by symport with a single proton over the range of external pH 6.5--7.7. The proton/lactose stoicheiometry has been measured directly over this pH range by comparison of the initial rates of proton and lactose uptake into anaerobic resting cell suspensions of E. coli ML308. Further, the relationship between the protonmotive force and lactose accumulation has been studied in E. coli ML308-225 over the range of external pH 5.9--… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
123
3

Year Published

1981
1981
2004
2004

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 40 publications
(49 reference statements)
12
123
3
Order By: Relevance
“…Increasing the external pH is known to simultaneously decrease ApH and increase At (15,16). Table 1 shows that At changes occurred in a similar manner between pH 6.9 and 8.2.…”
Section: "mentioning
confidence: 63%
“…Increasing the external pH is known to simultaneously decrease ApH and increase At (15,16). Table 1 shows that At changes occurred in a similar manner between pH 6.9 and 8.2.…”
Section: "mentioning
confidence: 63%
“…Further study of the presumed sucrose permease showed that it is most likely a sucrose/H+ syn-transporter as shown by similar stoichiometric ratios of H+ to [14C]sucrose uptake (0.83) to those of other syn-transporters such as the lactose permease of E. coli (West and Mitchell, 1973;Booth et al, 1979;Brooker et al, 1985) or the sucrose permease of Saccharomyces (Santos et al, 1982). Such a nearly stoichiometric ratio of H+ to sucrose transport further corroborates transport of sucrose by an active process, such as by a H+/sucrose syn-transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Internal pH was estimated by measuring the distribution of a weak acid (radiolabeled salicylic acid) across the membrane (4,8,23). Salicylate has been used by us and others as a reliable indicator of internal pH (13,24,26,34,47).…”
Section: Methodsmentioning
confidence: 99%